Chlorophyllum molybdites-synthesized manganese oxide nanoparticles (MnO-NPs): morphology, biocompatibility, and anticancer properties against liver cancer (HepG2) cell line - Irfan Ullah; Asif Kamal; Malka Saba; Ulfat Ara; Driss Touhami; Abdul Wahab; Tahir Maqbool; Moona Nazish; Abdulwahed Fahad Alrefaei; Maximilian Lackner (Scientific Reports)
Abstract Nanoparticles synthesized from natural sources are gaining prominence for their unique physicochemical properties and biocompatibility. This study investigates the potential of wild mushrooms, specifically Chlorophyllum molybdites (Lepiota morganii, green-spored parasol), for the green synthesis of manganese oxide nanoparticles. Mycosynthesized nanoparticles (NPs) were characterized via spectroscopic techniques such as XRD, UV spectroscopy, FTIR, and microscopic techniques such as SEM, and EDX, confirming their crystalline structure, spherical morphology, and a nanoscale size of 19.85 nm. FTIR analysis identified functional groups such as flavonoids, phenolics, and proteins, suggesting their role in nanoparticle stabilization and biological activity. Biocompatibility assays demonstrated minimal hemolysis (0.109 ± 0.05% at 400 µg/mL), indicating safety for biomedical use. Antileishmanial activity against Leishmania tropica (a flagellate parasite) revealed concentration-dependent inhibition, with IC50 values of 250 µg/ml and 224 µg/ml for promastigotes and amastigotes, correspondingly. Cytotoxic effects on HepG2 liver cancer cells were evaluated using MTT and crystal violet assays, showing significant dose-dependent reduction in cell viability (IC50 = 50 µg/mL) and apoptosis induction. Furthermore, comparative MTT assays confirmed enhanced efficacy of nanoparticles synthesized with Chlorophyllum molybdites. These results confirmed the multifaceted biomedical effeciacy of mycosynthesized nanoparticles, including anticancer and antiparasitic applications, while promoting sustainable nanoparticle synthesis.